Dietary Habits of Older Adults in Serbia: Findings From the National Health Survey - Dragana Stosovic; Nadja Vasiljevic; Verica Jovanovic; Andja Cirkovic; Katarina Paunovic; Dragana Davidovic (Frontiers Media S.A., 2021)
Objectives: Adults aged 65 years and older comprise one fifth of the Serbian population. Many of them have multiple, often diet-related comorbidities. We aimed to investigate their dietary habits by comparing them with younger adults' and to determine the relation of the differing ones to demographic, socioeconomic and health factors.Methods: We performed a secondary analysis of 2013 Serbian National Health Survey data on 14,082 adults. Binary logistic regression was used to determine dietary habits associated with older age (≥65 years) compared to younger age (18-64 years) and to assess their independent predictors in older adults.Results: Older adults more often reported everyday breakfast (OR = 2.085, 95%CI = 1.622-2.680) and brown/wholegrain bread consumption (OR = 1.681, 95% CI = 1.537-1.839), while using margarine (OR = 0.578, 95%CI = 0.397-0.839), discretionary salt (sometimes: OR = 0.648, 95%CI = 0.596-0.705, almost always: OR = 0.522, 95%CI = 0.445-0.614) and consuming fish (two or more times a week: OR = 0.465, 95%CI = 0.383-0.566) less frequently than younger adults. This was mainly positively related to urban environment, affluence, higher education and poor health.Conclusion: Using nationally representative data, we found that older adults reported healthier dietary habits compared to younger adults, which requires timely public health action.